2014
DOI: 10.1517/14740338.2014.939583
|View full text |Cite
|
Sign up to set email alerts
|

Cabazitaxel for metastatic castration-resistant prostate cancer: safety data from the Spanish expanded access program

Abstract: Cabazitaxel administration, in a real-world setting, is tolerated by Spanish patients with mCRPC, and the AEs are manageable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
3
9
1
3
Order By: Relevance
“…The incidence of grade ≥3 diarrhoea was low in our dataset (7.7%) and was similar to that in the TROPIC trial (6%) as well as other country's analyses (0.9%, 2.8%, 4.5%, 5.2% and 8.2% in the German, Italian, United Kingdom, Spanish and Canadian cohorts, respectively) . Diarrhoea, like neutropenia, requires patient education and proactive management .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The incidence of grade ≥3 diarrhoea was low in our dataset (7.7%) and was similar to that in the TROPIC trial (6%) as well as other country's analyses (0.9%, 2.8%, 4.5%, 5.2% and 8.2% in the German, Italian, United Kingdom, Spanish and Canadian cohorts, respectively) . Diarrhoea, like neutropenia, requires patient education and proactive management .…”
Section: Discussionsupporting
confidence: 85%
“…The rate of grade ≥3 neutropenia was much lower in the Australian EAP than in the TROPIC trial (20.2% vs 82.0%) . Similarly low rates of grade ≥3 neutropenia have been reported in analyses of the safety results from individual countries involved in the worldwide EAP and compassionate‐use program (CUP); 7.2%, 9.8%, 16.3% and 33.9% in the German, UK, Spanish and Italian cohorts, respectively . The lower frequency of neutropenia in the real‐world setting is most likely explained by the implementation of risk mitigation strategies including careful patient selection, patient education and proactive management including the prophylactic administration of G‐CSF …”
Section: Discussionmentioning
confidence: 74%
“…A number of early access programs (EAPs) involving 6.2%–26.8% of patients aged ≥75 years have demonstrated that cabazitaxel is well tolerated in a real-world setting 3235. In an Italian EAP, G-CSF was more frequently used in older patients (66.8% vs 58.0%), but the hematological tolerability of cabazitaxel seemed to be similar regardless of age 34…”
Section: Outcomes In Older Mcrpc Patients Treated With New Agentsmentioning
confidence: 99%
“…Ряд программ раннего доступа (EAP) с участием 6,2-26,8 % пациентов в возрасте старше 75 лет пока-зал, что кабазитаксел хорошо переносится в реальной клинической практике [30][31][32]. В итальянской EAP у пожилых пациентов чаще использовали Г-КСФ по сравнению с молодыми (66,8 % против 58,0 %), но частота гематологических нежелательных явлений не зависела от возраста больных [16].…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified